Effect of a Pipe Number on The Heat Transfer Rate For a Granit Stone Absorber Solar Collector - M. Mirmanto (JURNAL MECHANICAL, 2016)
As the fossil energy has been getting depletion, it is important to utilize alternative energies such as solar energy. An equipment that can be used for capturing and converting solar energy is solar collector. Two identical collectors used in this study were placed facing to the North with an inclination angle of 15°. The collector dimension was 0.8 m x 1 m x 0.05 m. One collector contained 5 parallel pipes and the other contained 7 parallel pipes.  The water used in the test was flowed naturally due to the gravity force from a higher tank and was adjusted using a valve fitted at the end of the collector. The water flow rates employed were 200, 250 and 300 cc/minutes and  measured using a volume meter and a stop watch. The results showed that the energy coming into the collector, energy absorbed by the absorber and water, increased with an increase in the observation time and reached the peak value at about  2.30 pm. After that, they decreased. The effect of the pipe number is significant and the performance of the collector containing 7 pipes is better than that containing 5 pipes.